Nigeria Local Government Autonomy and Economic Growth: The Path to Stable and Sustainable Federalism - Gbolahan Solomon Osho; Michael O. Adams (ASHA Publishing, 2025)
Local government autonomy is vital for governance and grassroots development in Nigeria, yet its effectiveness remains constrained by financial dependency, political interference, and weak institutions. This study investigates the relationship between local government autonomy and economic growth, situating Nigeria’s experience within fiscal federalism and decentralization theory. Using a comparative qualitative design with descriptive trend analysis, the research draws on data from the National Bureau of Statistics, Central Bank of Nigeria, FAAC reports, and case studies of Lagos, Enugu, Ogun, and Kogi States. Findings reveal that autonomous local governments, notably in Lagos and Enugu, demonstrate stronger capacity for internally generated revenue, infrastructure provision, employment creation, and poverty reduction, while less autonomous states such as Kogi underperform due to fiscal dependency and mismanagement. Comparative evidence from India and South Africa reinforces the importance of autonomy in stimulating service delivery and accountability. Policy implications emphasize the need for constitutional reforms to abolish the state–local joint account, direct funding mechanisms, stronger accountability frameworks, and capacity-building programs. Strengthening autonomy will enable local governments to function as agents of grassroots development, foster inclusive growth, and contribute meaningfully to Nigeria’s federal stability and sustainable economic transformation.